The Use of Polarization Filters to Detect the Edge of the Descemet’s Stripping Automated Endothelial Keratoplasty(DSAEK) Graft - Ide, Takeshi (Bentham Open, 2009)
PURPOSE: To report the technique of combining the two different polarization filters to detect the flap edge of the corneoscleral tissue before trephining the Descemet's stripping automated endothelial keratoplasty (DSAEK) tissue. METHODS: A human DSAEK donor tissue was prepared with mechanical microkeratome and the tissue on the cutting block was brought under the microscope. The liner, circular, or the combination of these two polarization filters was placed between the tissue and the microscope. The tissue images were taken with digital camera under either of 3 settings. RESULTS: The combination of circular and linear polarization filters enabled us to recognize the edge of the flap more easily than others. CONCLUSION: This simple system with polarization filters was effective in clear visualization of the flap edge during DSAEK tissue preparation. These features may significantly enhance safety of various surgical procedures, in addition to DSAEK tissue preparation.